Pedagogical strategies for developing interpretive language about images: A tertiary experience. Issue 1 (8th April 2019) - Ravelli, Louise
Abstract : Purpose: The purpose of this paper is to reflect on pedagogical strategies which support the teaching of critical analysis of visual and multimodal texts in a tertiary-level course for Arts students. Design/methodology/approach: The paper describes strategies which focus on developing students' abilities to express interpretive critique, as opposed to mere description. These strategies give students strong scaffolding towards success in their interpretive writing. The course in question is a tertiary-level Arts course which teaches Kress and van Leeuwen's (2006) approach to "reading images" in relation to contemporary media texts. The basic structure of the course is described, along with the macro steps which underpin the pedagogy. Examples of highly successful and less successful student writing are compared to reveal the key components of effective interpretive answers. Findings: In addition to the normal expectations regarding essay structure and style, and in addition to mastery of the technicality of the course, successful and less successful student writing depends on their mastery of a specific set of moves within the essay. These moves integrate textual observations with clear explanations and a strong relation to interpretation. Practical implications: While the course and strategies discussed are for tertiary-level students, the strategies described are adaptable to primary and secondary levels also. Multimodal texts are an integral part of the English curriculum, and all teachers need to explore strategies for enabling their students' critical engagement with such texts. Originality/value: Visual and multimodal texts are an exciting and also challenging part of English curricula, and new analytical frameworks and pedagogical strategies are needed to tackle these texts. In particular, the gap between simply describing visual resources (applying the tools) and critical analysis (using the tools) is vast, and specific pedagogical strategies are needed to help students develop the necessary interpretive language.